Littlewood–Paley Characterization for Musielak–Orlicz–Hardy Spaces Associated with Self-Adjoint Operators - Jiawei Shen; Shunchao Long; Yu-long Deng (Journal of Function Spaces)
Let X,d,μ be a metric measure space endowed with a metric d and a non-negative Borel doubling measure μ. Let L be a non-negative self-adjoint operator on L2X. Assume that the (heat) kernel associated to the semigroup e−tL satisfies a Gaussian upper bound. In this paper, we prove that the Musielak–Orlicz–Hardy space Hφ,LX associated with L in terms of the Lusin-area function and the Musielak–Orlicz–Hardy space HL,G,φX associated with L in terms of the Littlewood–Paley function coincide and their norms are equivalent. To do this, we first establish the discrete characterization of these two spaces. It improves the known results in the literature.